Assessing the Impact of Road and Land Use on Species Diversity of Trees, Shrubs, Herbs and Grasses in the Mountain Landscape in Southern Africa - Lisboa, Sá Nogueira; Domingos, Francisco; Vallius, Elisa; Lensu, Anssi; Macamo, Ernesto; Sitoe, Almeida (Frontiers in Conservation Science, 2022)
Mountain landscape, described as a global biodiversity hotspot due to high endemism, is threatened by land-use change, including management and modification of vegetation. However, there is little knowledge about how road and land use affect plant diversity in mountains landscapes, particularly in southern Africa. Previous studies have studied the impact of the road or land use on plant species diversity separately and have concentrated on a single plant species. Here we compare the plant diversity of regenerated trees, shrubs, herbaceous plant, and grasses among Forest, Fallow, Agriculture, and Road in the Moribane Forest Reserve (MFR), in Eastern Chimanimani Mountain landscape in Mozambique. To assess how land-use change affects plant diversity, we conducted 45 transects along the roadside and randomly established 24 quadrats in the Agriculture fields and Fallow and 26 quadrats in the pristine Forest. In each transect and quadrats, we recorded the occurrence of four plant life forms (regenerated trees, shrubs, herbaceous, and grass species) to determine the alpha and beta-diversity across land-uses, and we assessed the invasiveness of each species. Species composition varied significantly among the land-uses types. Roadside had higher species diversity and the highest number of invasive species (138 total species of all plant life forms; 31 invasive species), following Agriculture (72; 30), Fallow (81; 20), and Forest (78; 19). There was no similarity in species between roadsides and other land-uses. Furthermore, roadside recorded the highest average species turnover for all plant life forms following Agriculture, Forest, and Fallow. Among the plants, the most important life form was herbaceous with 143 species, following grass with 86 species, shrubs with 86, and regenerated trees with 65 species. The land-use pattern makes the landscape more diversified in the study area and, as a result, increase the plant species richness and diversity by species replacement. This study is unique in collecting and analyzing data on different plant life forms on roadsides linked with a range of different land-use types within a small region of a mountain landscape in southern Africa.